IoT-Based Automatic Fire Protection System (SIPEKA) with Android Application for Fast Monitoring and Response - Jenie Sundari; Yunita Yunita; Popon Handayani; Sifa Fauziah; Hardiyan Hardiyan (ZERO: Jurnal Sains, Matematika dan Terapan, 2025)
Fire hazards cause serious damage, especially in densely populated areas lacking rapid-response systems. This study introduces SIPEKA, an IoT-based automatic fire suppression system integrated with an Android application for real-time monitoring and control. The system uses DHT22 and MQ-2 sensors connected via Wi-Fi to detect fire indicators and activate suppression devices such as pumps or sprinklers. Testing was conducted in a controlled 3×3 m residential-like environment. Results show an average fire detection time of 2.8 s, a notification delay of 1.5 s, and a suppression success rate of 94.7%. The Android interface provides reliable manual override and remote monitoring with 99% uptime. Unlike conventional IoT fire systems that only issue alerts, SIPEKA combines automatic suppression, mobile control, and real-time monitoring, offering an effective, low-cost, and intelligent solution to improve household fire safety.